Round the Bend - Clarkson, Jeremy (London Michael Joseph an Imprint of Penguin Books, 2011)
Explores the world from the safety of four wheels. This title shows how the world of performance cars may be likened to Battersea Dogs' Home. It reveals why St Moritz may be the most bonkers town in all of the world.
Keywords: Automotive journalism -- English wit and humor